2000
DOI: 10.1046/j.1439-0434.2000.00530.x
|View full text |Cite
|
Sign up to set email alerts
|

Function of Host and Fungal Metabolites in Resistance Response of Banana and Plantain in the Black Sigatoka Disease Pathosystem (Musaspp. –Mycosphaerella fijiensis)

Abstract: The hostÐpathogen interactions of Musa spp[ and Myco! sphaerella _jiensis were investigated in order to determine the function of secondary metabolites within the patho! system of the Black Sigatoka disease[ The pentaketide metabolites~aviolin\ 1!hydroxyjuglone\ juglone and 1\3\7!trihydroxytetralone "1\3\7!THT# of the pathogen were identi_ed[ The concentration of 1\3\7!THT was sig! ni_cantly increased by application of the synthetic com! pound tricyclazole and by natural activators extracted from the intercell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
41
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 22 publications
2
41
0
1
Order By: Relevance
“…It produces a number of low molecular weight secondary metabolites (i.e., fijiensine, tetralone, juglone), which are toxic to banana plants (Molina and Krausz, 1988;Stierle et al, 1991;Harelimana et al, 1997;Lepoivre, 2000;Hoss et al, 2000). These metabolites are suspected of contributing to disease progression (Lepoivre, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It produces a number of low molecular weight secondary metabolites (i.e., fijiensine, tetralone, juglone), which are toxic to banana plants (Molina and Krausz, 1988;Stierle et al, 1991;Harelimana et al, 1997;Lepoivre, 2000;Hoss et al, 2000). These metabolites are suspected of contributing to disease progression (Lepoivre, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The symptoms of the disease include elongated, necrotic lesions surrounded by chlorotic zones, suggesting the involvement of phytotoxins (Upadhyay et al 1990). Mycosphaerella fijiensis is known to produce lipophilic phytotoxins (Hoss et al 2000;Stierle et al 1991;Upadhyay et al 1990); 2,4,8-trihydroxytetralone is the most abundant and the most phytotoxic, with a hostselectivity similar to that of the pathogen (Stierle et al 1991). The mechanism of action of the different lipophilic phytotoxins produced by M. fijiensis has been studied very little; however, it has been reported that their activity is light-dependent, they affect the chloroplast, and disturb the proton electrochemical gradient across the plasma membrane, increase electrolyte leakage, and induce an oxidative burst in Musa spp.…”
Section: Introductionmentioning
confidence: 99%
“…to M. fijiensis is related to the post-infection activation of different defense mechanisms in the plant, e.g. production of proteins related to pathogenesis (Lepoivre et al 1993), hypersensitive response (Mourichon et al 1997), changes in the structure of preformed metabolites (Hoss et al 2000), and production of phytoalexins (Quiñones et al 2000). Even though a number of phytoalexins have been reported from the crop (e.g.…”
mentioning
confidence: 99%